Intracranial pressure in primary open angle glaucoma, normal tension glaucoma, and ocular hypertension: a case-control study - Berdahl, John P; Fautsch, Michael P; Stinnett, Sandra S; Allingham, R Rand (Investigative ophthalmology & visual science, 2008)
To compare intracranial pressure (ICP) in subjects with primary open-angle glaucoma (POAG), normal-tension glaucoma (NTG; subset of POAG), and ocular hypertension (OHT) with that in subjects with no glaucoma. The study was a retrospective review of medical records of 62,468 subjects who had lumbar puncture between 1985 and 2007 at the Mayo Clinic. Of these, 57 POAG subjects, 11 NTG subjects (subset of POAG), 27 OHT subjects, and 105 control subjects met the criteria and were analyzed. A masked comparison of the relationship between ICP and other ocular and nonocular variables was performed by using univariate and multivariate analyses. ICP was significantly lower in POAG compared with age-matched control subjects with no glaucoma (9.1 +/- 0.77 mm Hg vs. 11.8 +/- 0.71 mm Hg; P < 0.0001). Subjects with NTG also had reduced ICP compared with the control subjects (8.7 +/- 1.16 mm Hg vs. 11.8 +/- 0.71 mm Hg; P < 0.01). ICP was higher in OHT than in age-matched control subjects (12.6 +/- 0.85 mm Hg vs. 10.6 +/- 0.81 mm Hg; P < 0.05). ICP is lower in POAG and NTG and elevated in OHT. ICP may play an important role in the development of POAG and NTG and in preventing the progression of OHT to POAG. Further prospective and experimental studies are warranted to determine whether ICP has a fundamental role in the pathogenesis of glaucoma.